Single-crossing, strategic voting and the median choice rule - Alejandro Saporiti; Fernando Tohmé (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2003)
This paper studies the strategic foundations of the Representative Voter Theorem (Rothstein, 1991), also called the second version of the Median Voter Theorem. As a by-product, it also considers the existence of non-trivial strategy-proof social choice functions over the domain of single-crossing preference profiles. The main result presented here is that single-crossing preferences constitute a domain restriction on the real line that allows not only majority voting equilibria, but also non-manipulable choice rules. In particular, this is true for the median choice rule, which is found to be strategy-proof and group-strategic-proof not only over the full set of alternatives, but also over every possible policy agenda. The paper also shows the close relation between single-crossing and order-restriction. And it uses this relation together with the strategy-proofness of the median choice rule to prove that the collective outcome predicted by the Representative Voter Theorem can be implemented in dominant strategies through a simple mechanism in which, first, individuals select a representative among themselves, and then the representative voter chooses a policy to be implemented by the planner.
Keywords: D70; D71; D78; 330; single-crossing; order-restriction; median voter; strategy-proofness; Neue politische Ökonomie; Medianwähler-Modell